Теоретичні засади іншомовної підготовки фахівців соціальної сфери в європейському освітньому просторі - Павелків, Катерина (My University, 2019)
Мета дослідження: схарактеризувати теоретичні засади іншомовної підготовки фахівців соціальної сфери в європейському освітньому просторі. У статті здійснено системний аналіз теоретичних засад іншомовної підготовки фахівців соціальної сфери в європейському освітньому просторі, що дало змогу виокремити й схарактеризувати ряд провідних принципів іншомовної підготовки майбутніх фахівців соціальної сфери в країнах Євросоюзу у контексті компетентнісного підходу. Методи дослідження. Для реалізації мети дослідження використано комплекс взаємопов’язаних та взаємодоповнюючих методів дослідження: аналіз, синтез, порівняння та узагальнення – для виявлення теоретичних засад іншомовної підготовки фахівців соціальної сфери; аналітичний, що забезпечив системний аналіз літературних, документальних та інших англомовних джерел, систематизацію, порівняння та узагальнення; пошуковий, що використовувався для формування узагальнених висновків, оцінок, виявлення раціонального і практично-ціннісного в наукових розробках з проблеми. Результат. Визначені теоретичні засади іншомовної підготовки фахівців соціальної сфери в європейському освітньому просторі можуть бути використані для вирішення завдань іншомовної підготовки фахівців соціальної сфери у закладах вищої освіти.The purpose of the research: to characterize theoretical foundations of foreign language training of social sphere specialists in European educational area. System analysis of theoretical foundations of foreign language training of social sphere specialists in European educational area was carried out, that made it possible to distinguish and characterize the main factors determining the need and ensuring effective implementation of foreign language training of future social sphere specialists in higher education of the countries of the European Union. A number of key principles of foreign language training of future social sphere specialists in the countries of the European Union were distinguished and it was also characterized a foreign language training of mentioned specialists in the context of modern competence approach that results in a high level of their leading competencies. It was clarified that a foreign language training of social sphere specialists in the educational establishments of the European Union countries is characterized as a cognitive, values oriented, communicative, esthetic and transformative activity. Research methods. To fulfil the research purpose the complex of interconnected and complementary research methods was used: analysis, synthesis, comparison and generalization – to discover the theoretical foundations of foreign language training of social sphere specialists; analytical that provided system analysis of literary, documentary and other English sources, systematization, comparison and generalization; research that was used for the formation of generalized conclusions, assessments, discovering of rational and practical and value in scientific investigations on the problem. The result. It was determined the theoretical foundations of foreign language training of social sphere specialists in European educational area, that can be used for the problems solving of foreign language training of social sphere specialists in higher educational establishments.
Keywords: іншомовна підготовка; foreign language training; фахівці соціальної сфери; теоретичні засади; європейський освітній простір; social sphere specialists; theoretical foundations; European educational area